Effect of Viscous Dissipation on Unsteady MHD Free Convection Mass Transfer Flow of Polar Fluid over a Vertical Porous Plate in Presence of Thermal Diffusion and Heat source - P.Pramod kumar, Bala Siddulu Malga, Sweta Matta, Lakshmi Appidi (International Journal of Advanced Science and Technology, 2020)
In present research paper effect of viscous dissipation on unsteady polar fluid of free convection flow of heat and mass transfer past a vertical semi- infinite plate moving in porous medium, within the existence of transverse magnetic field is studied. Velocity of the plate is constant in the longitudinal direction. Governing dimensional partial differential equations are converted to dimensionless using similarity variables. Dimensionless expressions of velocity, angular velocity, temperature and concentration are solved by applying Galerkin finite element technique. Impact of Eckert number and flow parameters on Velocity, Micro rotation and Temperature profiles are explained via graphs. Skin friction, rate of heat transfer is studied.